Delitos Informáticos - Villavicencio Terreros, Felipe A. (Pontificia Universidad Católica del Perú, 2014)
In recent times, due to the development of information technology,a new form of crime called informational crimes has developed. in relation to this new type of crime, a special criminal law was issued, whose purpose is to prevent and punish illegal activities that affect computer systems and datas, secret communications, and other legal goods that are affected withthis type of crime, such as equity, public faith and sexual freedom.

En los últimos tiempos, producto del desarrollo de las tecnologías informáticas se ha ido desarrollando una nueva forma de criminalidad denominada delitos informativos. en relación a esta nueva forma delictiva, se ha emitido una Ley penal especial cuya finalidad es prevenir y sancionar las conductas ilícitas que afectan los sistemas y datos informáticos, así como el secreto de las comunicaciones, y los demás bienes jurídicos que resulten afectados con esta modalidad delictiva, como son el patrimonio, la fe pública y la libertad sexual.
Cybercrimes
Keywords: Law; Cybereducation; Cybercriminal; Hackers; Crackers; Informatics Sabotage; Worms; Malware; Browser; Cookie; Dialup; Cibereducación; Ciberdelincuente; Hackers; Crackers; Sabotaje Informático; Gusanos; Malware; Browser; Cookie; Dialup; https://purl.org/pe-repo/ocde/ford#5.05.00